设f(x)的一个原函数是e-x,则∫xf(x)dx=()。
A: e-x(x-1)+c
B: e-x(x+1)+c
C: -e-x(x-1)+c
D: -e-x(x+1)+c
A: e-x(x-1)+c
B: e-x(x+1)+c
C: -e-x(x-1)+c
D: -e-x(x+1)+c
举一反三
- 若f(x)的一个原函数是e-x,则不定积分∫xf(x)dx等于______ A: e-x(x+1)+C B: e-x(1-x)+C C: e-x(x-1)+C D: -e-x(x+1)+C
- 若∫f(x)dx=xe-x+C,则f(x)=______ A: (1-x)e-x B: (x-1)e-x C: xe-x D: -xe-x
- 若∫f(x)dx=F(x)+C,则∫e-xf(e-x)dx=______. A: B: A.F(e-x)+C C: B.F(ex)+C D: C. E: D.-F(e-x)+C
- 设F(x)是f(x)的一个原函数则∫e-xf(e-x)dx=() A: -F(ex)+c B: -F(e-x)+c C: F(ex)+c D: F(e-x)+c
- 设F(x)是f(x)的一个原函数,则∫e-xf(e-x)dx等于()。 A: F(e-x)+C B: -F(e-x)+C C: F(ex)+C D: 一F(ex)+C